Factors Related to Willingness of Village Midwifes to Work and to Stay in the Village in Tangerang District, Banten Province Year 2003 - Sandra Fikawati; Wastidar Musbir; Ahmad Syafiq (Makara Journal of Health Research, 2010)
One important effort that has been implemented by the Government of Indonesia to accelerate the reduction of MMR (Maternal Mortality Rate) and IMR (Infant Mortality Rate) in Indonesia is narrowing the distance between health care services and community including placement of village midwives (BDD). This study is a cross-sectional quantitative study aimed to investigate factors related to the willingness of BDDs to work and stay in the villages of Tangerang District. Data were collected in July 2003 from 120 BDDs (among a total of 196 BDDs in Tangerang District or 61.2%) through self-administered questionnaires. The study found that marital status, length of work, motivation to continue study, location of husband's work, community support, and community health center's support were factors significantly related to BDD willingness to work and stay in the village. The most dominant factors were length of work, motivation to study again, location of husband's work, and health center support. Those factors are to be considered if BDD is going to be sustained in the village. Government, both central and local, and professional institution such as Indonesia Midwives Association and academic institution should collaborate to prevent the attrition of BDD from villages where their existence is mostly needed.